EFEKTIVITAS ANTIDIABETES EKSTRAK DAUN KAYU MANIS (Cinnamomum burmanni) PADA MENCIT PUTIH JANTAN - Diza Sartika; Miftahur Rahmi; Ringga Novelni; Fatma Adilla (JURNAL KATALISATOR, 2023)
Cinnamon leaf extract (Cinnamomum burmanni) contains flavonoid compounds that function to stimulate insulin activation so that it can be used for anti-hyperglycemia.The purpose of this study was to determine the effect of giving cinnamon leaf extract (Cinnamomum burmanni) to male white mice induced by dexamethasone and 10% glucose and to determine the effective dose of cinnamon leaf extract (Cinnamomum burmanni) which can reduce blood glucose levels in mice. hyperglycemia. The group was divided into 6 groups, consisting of negative control, positive control, dose variation of 250mg/kg bw, 500mg/kg bw and 750mg/kg bw and the comparison group was Glibenclamide. The inducer used was dexamethasone 5mg/ml and 10% glucose. Induction of dexametason is carried out for 6 days and continued the administration of 10% glucose for 2 days, then given test preparations from days 7, 14 and 21 after the induction of dexamethasone and glucose 10%.  The results showed that the best dose in reducing blood sugar levels in mice was a dose of 750 mg/KgBW with a percentage reduction of 26.33%. Two-way ANOVA statistical analysis test on the percentage of significant antidiabetic (p<0.05). The conclusion of this study is that the ethanolic extract of cinnamon leaves has the effect of activity in lowering blood glucose levels on the 21st day.